Deposition Measurements From the Full-Scale Radiological Dispersal Device Field Trials. Issue 5 (May 2016) - Erhardt, Lorne; Lebel, Luke; Korpach, Ed; Berg, Rodney; Inrig, Elizabeth; Watson, Ian; Liu, Chuanlei; Gilhuly, Colleen; Quayle, Debora
Abstract : Abstract: In 2012, Defence Research and Development Canada led a series of experiments, titled the Full-Scale Radiological Dispersal Device Field Trials, in which short-lived radioactive material was explosively dispersed and the resulting plume and deposition were characterized through a variety of methods. Presented here are the results of a number of measurements that were taken to characterize the radioactive ground deposition. These included in situ gamma measurements, deposition filter samples, and witness plate measurements that were taken in situ with handheld beta survey meters. The results from the different measurement techniques are compared to each other and to a simple deposition model. Results showed that approximately 3% of the original source activity was deposited in the immediate vicinity of ground zero, and an additional 15–30% of the original activity was deposited within 450 m of ground zero. Implications of these results for emergency response are discussed.